Association of Hypertension With the Risk and Severity of Epistaxis - Byun, Hayoung (JAMA Otolaryngol Head Neck Surg, 2020)
IMPORTANCE: The association between hypertension and epistaxis has long been a subject of debate. OBJECTIVES: To evaluate the risk of epistaxis in patients with hypertension using a nationwide population cohort and to assess the association of hypertension with the methods of managing cases of epistaxis. DESIGN, SETTING, AND PARTICIPANTS: In this retrospective cohort study, a hypertension cohort and comparison cohort were built using the Korean National Health Insurance Service–National Sample Cohort that represents the entire population of the Republic of Korea from January 1, 2002, to December 31, 2015. The hypertension cohort comprised 35 749 patients with a record of 3 or more prescriptions of antihypertensive medication and a diagnosis of hypertension (International Statistical Classification of Diseases and Related Health Problems, Tenth Revision code I10). Patients with other diseases associated with epistaxis, such as sinonasal tumors, facial trauma, bleeding tendency, and coagulation disorder, as well as those taking anticoagulant medications, were excluded. A comparison cohort comprised 35 749 individuals without hypertension matched sociodemographically in a 1:1 ratio. Statistical analysis was performed from January 1, 2019, to March 31, 2020. MAIN OUTCOMES AND MEASURES: The incidence and recurrence of epistaxis were evaluated in both cohorts. The risk factors for epistaxis and management strategies were also assessed. RESULTS: Among the 35 749 patients in the hypertension cohort (20 579 men [57.6%]; median age, 52 years [interquartile range, 45-62 years]) the incidence rate (IR) of epistaxis was 32.97 per 10 000 persons (95% CI, 30.57-35.51 per 10 000 persons); among the 35 749 individuals in the comparison cohort (20 910 men [58.5%]; median age, 52 years [interquartile range, 45-62 years]), the IR of epistaxis was 22.76 per 10 000 persons (95% CI, 20.78-24.89 per 10 000 persons) (IR ratio, 1.45; 95% CI, 1.29-1.63; adjusted hazard ratio, 1.47; 95% CI, 1.30-1.66). The IR of recurrent epistaxis was 1.96 per 10 000 persons in the hypertension cohort and 1.59 per 10 000 persons in the nonhypertension cohort (IR ratio, 1.23; 95% CI, 0.77-2.00). Patients with hypertension who experienced epistaxis were more likely to use the emergency department (odds ratio, 2.69; 95% CI, 1.70-4.25; Cohen h effect size, 0.27; 95% CI, 0.16-0.39) and receive posterior nasal packing (odds ratio, 4.58; 95% CI, 1.03-20.38; Cohen h effect size, 0.15; 95% CI, 0.03-0.26) compared with the comparison cohort. CONCLUSIONS AND RELEVANCE: This study suggests that patients with hypertension had an increased risk of epistaxis requiring hospital visits. In addition, epistaxis in patients with hypertension appeared to need more emergency department visits and require more posterior nasal packing procedures compared with patients without hypertension. Medical counseling about epistaxis is advisable for individuals with hypertension, and the presence of hypertension should be considered in managing nasal bleedings.